(untitled) (Global Journal of Management and Business Research, 2016)
The cancellation of the N100 charge per unit withdrawal from ATM on December 17, 2012 in Nigeria has the capacity to reduce cash demand, in line with the prediction of the Tobin-Baumol model of cash inventory/money demand. This possible effect of the cancellation policy on effectiveness of the Central Bank of Nigeria’s (CBN) Cash Policy in terms of cash demand reduction is yet to be thoroughly examined and documented in the literature. This study fills the gap by examining the effects of the policy that cancelled the ATM withdrawal charges on cash demand and effectiveness of the Cash Policy, using data collected from 200 bank customers in Osogbo, Osun state. The results show that the cancellation policy reduced idle cash balances as people felt free to withdraw as many times as desired since there was no penalty on frequent withdrawals. The study thus concluded that the cancellation of ATM charges and the engendered reduction in cash demand may enhance the Cash Policy, while the policy that re-imposed penal charges may undermine it.